Accelerating 3D printing for surface wettability research - Fernández-Rodríguez, Jose David; De Coninck, Joël (My University, 2016)
The wettability of a surface is affected by its physical and chemical properties, but it can be modulated by patterning it. Researchers use many different techniques for surface patterning, each one with different trade-offs in terms of cost, flexibility, convenience and realizable geometries. Very high-resolution 3D printing technologies (such as stereolithography by two-photon absorption) have the potential to greatly increase the range of realizable surface geometries, but they are currently not in wide use because they are too slow for printing the relative large surface areas required for wetting experiments. To enable the use of these 3D techniques, we are developing new slicing algorithms able to speed up 3D-printing technologies.
Keywords: Impresión tridimensional; 3d printing; Multiresolution